PENGARUH PENGAWASAN, KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. ADEI PLANTATION & INDUSTRI KEBUN MANDAU SELATAN - Novriani '; Susi Hendriani; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to determine the effect Influence of supervision, organizational commitment, and job satisfaction on employee discipline on PT. Adei Plantation& Industry Kebun Mandau Selatan.The population in this study 49 people. While the sampling technique with cluster sampling method is to take a census of all employees. Data were analyzed using multiple linear regression method with SPSS 18. Based on the survey results revealed that the supervisory, organizational commitment, and job satisfaction significant effect partially and simultaneously to discipline employees of PT. Adei Plantation& Industry Kebun Mandau Selatan.Keywords : Supervision, Organizational, Commitment, Job Satisfaction and Work Discipline.